2012
DOI: 10.1345/aph.1r020
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandin Resistance inCandidaSpecies: Mechanisms of Reduced Susceptibility and Therapeutic Approaches

Abstract: B loodstream infections caused by Candida spp. or candidemia are the fourth most common cause of nosocomial bloodstream infections in the US. 1 Candidemia is associated with mortality rates approaching 50% and health care costs exceeding $40,000 per incident. 1-3 C. albicans is the most commonly isolated species; however, the incidence of non-C. albicans spp. has increased over the past 2 decades. 4,5 Non-C. albicans spp., including C. glabrata and C. krusei, are associated with higher rates of antifungal resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 70 publications
(73 reference statements)
4
66
0
Order By: Relevance
“…The clinical impact of misidentifying C. albicans as C. dubliniensis is likely to be minimal, although it has been suggested that the development of fluconazole resistance is more likely for C. dubliniensis than for C. albicans (31). C. parapsilosis exhibits higher MICs for the echinocandins than do most other Candida species (8,32); therefore, misidentification might be clinically significant. However, data on the susceptibility profile of C. pelliculosa are sparse, and it is not obvious what empirical therapy might be initiated based on this identification.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical impact of misidentifying C. albicans as C. dubliniensis is likely to be minimal, although it has been suggested that the development of fluconazole resistance is more likely for C. dubliniensis than for C. albicans (31). C. parapsilosis exhibits higher MICs for the echinocandins than do most other Candida species (8,32); therefore, misidentification might be clinically significant. However, data on the susceptibility profile of C. pelliculosa are sparse, and it is not obvious what empirical therapy might be initiated based on this identification.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for the high MIC values for CAS is unclear (45) . Recent works have described a functional point mutation in the glucan synthase (FKS) gene of the C. parapsilosis complex species, which may explain this observation (46) (47) . FKS gene mutations have been shown to be associated with resistance to CAS, as demonstrated by increases in MICs in mutant isolates compared with those of wild-type isolates (48) (49) (50) .…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%
“…In contrast, pathogenic fungi resistant to azole and echinocandin antifungal drugs are now a serious concern. [1][2][3][4] These traits make AMB an ideal therapy for patients with unidentified invasive fungal infections.…”
Section: Introductionmentioning
confidence: 99%